Refractive-diffractive hybrid optics array: comparative analysis of simulation and experiments - Low, Mun Ji (2022)
Hybrid optical elements, which combine refractive and diffractive optical components to enhance optical performance by taking advantage of the optical characteristics of the individual components, have enormous potential for next-generation optical devices. However, there have not been many reports on the simulation methodology to characterize such hybrid optical systems. Here, we present a method for simulating a hybrid optical element realized by attaching an ultra-thin, flexible diffractive optics array onto a refractive optical element. The ultra-thin diffractive optical element is fabricated by direct-laser-writing using a femtosecond pulsed laser as the light source. A systematic investigation of the proposed simulation method, which does not require extensive hardware resources or computational time, but retains resolution and accuracy, is presented. The proposed scheme is validated by comparing simulation and experimental results. The simulation and experimental results on the spot size and focal length for the diffractive Fresnel zone plate (FZP) match well, with typical errors of less than 6%. The aspect ratio of the focal spot sizes at the compound and FZP focal planes of the hybrid optical system from the simulation and experiment also match quite well, with typical errors below 7%. This simulation scheme will expedite the designs for novel hybrid optical systems with optimal optical performances for specific applications, such as microfluidics and aberration-controlled optics.